Uncertainty in Teacher Education Futures Scenarios, Politics and STEM - Schuck, Sandy (Springer Singapore, 2018)
This book discusses the use of futures methodologies to examine and critique teacher education and investigate drivers of change in teacher education contexts, providing readers with futures tools that they can use to explore curricula and pedagogies. It explains futures methods, including scenario development and backcasting, and illustrates them with examples of research in science, technology and mathematics education contexts. By allowing the long-term influence of current trends to be considered and providing an opportunity to reflect on the present and imagine the future, scenarios provoke discussion on the directions that teacher education might take now. The book offers insights into the possibilities that might exist for teacher education futures and into how scenario building and planning can be used to inform debates about the present. Further, it suggests ways in which readers can influence the future of teacher education through understanding the drivers of change.